2003
DOI: 10.1080/312703002235
|View full text |Cite
|
Sign up to set email alerts
|

B Lind T Racheal I Ntubation by P Aramedics Through the Lma-U Nique

Abstract: In this study, when attempting blind tracheal intubation through the LMA-Unique, paramedics were rarely successful in tracheal placement. Basic LMA-Unique insertion, however, had a very high success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These figures are quite similar to our findings. Although one study with LMA Unique™ insertions by paramedics reported high success rate (96%) 17 , these subjects had prior experience using the LMA Classic™. We have not come across papers reporting novice use of SoftSeal™.…”
Section: Table 2 Order Of Mask Insertions As Randomly Selected By Novice Staffmentioning
confidence: 96%
“…These figures are quite similar to our findings. Although one study with LMA Unique™ insertions by paramedics reported high success rate (96%) 17 , these subjects had prior experience using the LMA Classic™. We have not come across papers reporting novice use of SoftSeal™.…”
Section: Table 2 Order Of Mask Insertions As Randomly Selected By Novice Staffmentioning
confidence: 96%
“…In 2000, Fan et al 15 found an intubation success rate through the ILMA of only 76%, which is a lower success rate than we found. A study by Barnes et al,16 looking at intubation through the LMA-Unique TM by paramedics, had an intubation success rate of only 21%, which indicates the advantage of using the ILMA, which has been specifically designed as an tracheal intubation aid.…”
Section: Discussionmentioning
confidence: 94%
“…Blind intubation techniques through LMA report a variable success rate (30-93%),[ 25 ] while the most used GEB-aided technique varies from 27.5% to 63%. [ 22 26 27 28 ]…”
Section: Discussionmentioning
confidence: 99%